Perilaku Ibu Dalam Pemberian Asi: Studi Tafsir Shofwah At-Tafaasiir - aprilia, yosella cindy; shomad, bukhori abdul; windari, fitri (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2026)
Breastfeeding is a crucial early stage in achieving a healthy and prosperous life for a child. However, some mothers, particularly among socialites and Generation Z young mothers, are reluctant to breastfeed due to concerns over changes in body shape, especially weight gain, leading them to choose formula milk as an alternative. This study aims to examine in depth the behavior of mothers who are reluctant to breastfeed for these reasons, using the Tafsir Shofwah At-Tafaasiir approach to Quranic verses related to breastfeeding. This article employs a thematic interpretation (tafsir maudhu’i) method with a library research approach. Data were collected from various literary sources, such as the Qur’an, tafsir books, scientific literature, journals, and relevant theses. The collected sources were analyzed through reading and quoting to formulate the research conclusions. The findings indicate that breastfeeding for two full years is a form of maternal responsibility and affection that should not be unilaterally discontinued without the husband's agreement and consideration of the child’s best interest. Breastfeeding is also beneficial for the mother's health, including reducing the risk of cancer and aiding postnatal recovery.